2012
DOI: 10.1088/0957-4484/23/4/045601
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach to the fabrication of Au/silica core–shell nanostructures based on nanosecond laser irradiation of thin Au films on Si

Abstract: We demonstrate the possibility of producing Au/SiO(2) core-shell nanoparticles by nanosecond laser irradiation of thin (5 and 20 nm) Au films on Si. The Au/Si eutectic reaction and dewetting process caused by the fast melting and solidification dynamics induced by the nanosecond laser irradiations are investigated as the origin of the formation of core-shell nanoparticles. Using several microscopic techniques (Rutherford backscattering spectrometry, scanning electron microscopy, atomic force microscopy, transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…A wide range of materials can be used for the fabrication of nanocrystals by dewetting, such as metals or semiconductors. In addition, the structure of the dewetted layers can be controlled using several techniques such as pulsed laser annealing [35,36] or a substrate patterned by focused ion beam. The study of Ge dewetting on SiO 2 [37] has already been reported in the literature, however, only in the case of very thin amorphous Ge layers (5−15 nm thick) [38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of materials can be used for the fabrication of nanocrystals by dewetting, such as metals or semiconductors. In addition, the structure of the dewetted layers can be controlled using several techniques such as pulsed laser annealing [35,36] or a substrate patterned by focused ion beam. The study of Ge dewetting on SiO 2 [37] has already been reported in the literature, however, only in the case of very thin amorphous Ge layers (5−15 nm thick) [38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Au films deposited on SiO 2 substrates are thermodynamically unstable [25] (i.e. the spreading coefficient is negative) so that solid-state dewetting process of the Au films is expected upon annealing at temperature below the Au melting temperature [25][26][27][28][29][30][31]. From a general point of view [34][35][36][37], the dewetting process is driven by the minimization of the free energy of the system: the continuous film decay in NPs with the same total volume but less surface area.…”
Section: Resultsmentioning
confidence: 99%
“…The dewetting process is driven by the minimization of the free energy of the system and leads to the formation of metal NPs (form the continuous as-deposited film) on the substrate surface. The kinetic mechanism of thin film dewetting has been described in detail for a flat substrate [25][26][27][28][29][30][31]. In the case presented in this work, the dewetting of the Au film occurs on a curved substrate (the SiO 2 NWs surface) leading, nevertheless, to the formation of Au NPs coating the SiO 2 NWs.…”
Section: Introductionmentioning
confidence: 92%
“…For a detailed discussion of the mechanisms of nanostructuring along with the modeling of results see ref. [31][32][33][34] The origin of the RT instabilities is due to exposition to an external energy flux at the interface between the material layers of different densities. The radius of droplets created as a result of room temp.…”
Section: Structure Of Np Arraysmentioning
confidence: 99%